Islamic Tolerance as an Ethics o Islamic Tolerance as an Ethics of Coexistence in Muḥammad ʿImārah’s Thought - Rohman, Muhammad Ainur; Ulum, M. Miftahul; Agustia, Zennanta; Rivaldi, Muhammad Fauzan; Rifai, Mohammad Rohman; Zahiduzzaka, Muhammad Faza; Arofat, Muchtar; Zarkasyi, Ziad Ahmad (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Debates on Islamic tolerance continue to turn on the relation between doctrinal conviction, freedom of conscience, and public coexistence in plural societies. This article examines how Muḥammad ʿImārah’s Al-Samāḥah al-Islāmiyyah constructs Islamic tolerance as coexistence ethics. Using directed qualitative content analysis, the study analyzes textual units concerning Qur'anic non-coercion, the Medina Charter, the Najran Covenant, historical coexistence, and critiques of coercive exclusivism. The analysis shows that ʿImārah organizes tolerance through four interrelated categories: theological non-coercion, constitutional pluralism, active protection of religious communities, and historical participation in Islamic civilization. Its contribution lies in reading Al-Samāḥah al-Islāmiyyah as a unified textual construction that links faith, law, citizenship, protection, and participation. Indonesia is used only as a theoretical context for discussing the relevance of these categories to religious moderation and national coexistence, not as an empirical field site. The article argues that al-samāḥah can function as an Islamic ethical-political vocabulary for defending religious freedom, inclusive citizenship, minority protection, and interfaith solidarity in plural societies.